A study of wellbore cement alteration controlled by CO2 leakage in a natural analogue for geological CO2 storage. (November 2017) - Hernández-Rodríguez, Ana; Montegrossi, Giordano; Huet, Bruno; Vaselli, Orlando; Virgili, Giorgio
Abstract: This study presents the results obtained by studying well integrity in the natural analogue for the geological storage of CO2 of Sant'Albino, Southern Tuscany, which is affected by intense CO2 degassing and where a thermal spa and a CO2 production plant are present. Reaction Path Modeling (RPM) of cement hydration and carbonation as well as Reactive Transport Modeling (RTM) of cement alteration were used to investigate the processes occurring near a hypothetical average production well with a damaged leaking zone, affecting casing and cement, assuming a defined composition of class G Portland cement. It turns out that the advective flow of CO2 from the damaged zone, first, leads to completion of cement carbonation and, second, promotes further cement alteration through considerable dissolution of carbonate minerals. These processes takes place in a relatively short time, in the order of some years. The ultimate consequence of these CO2 -promoted comparatively fast chemical reactions is most likely CO2 leakage to the surface. Highlights: Advective flow of CO2 occurring through casing damage zone affect cement integrity. Cement alteration promotes through considerable dissolution of carbonate minerals. These CO2 -promoted reactions cause alteration of large cement amounts in short time. These chemical reactions may trigger a CO2 leakage to the surface.